Cecal ligation and puncture accelerates development of ventilator-induced lung injury - Yehya, Nadir (Am J Physiol Lung Cell Mol Physiol, 2014)
Sepsis is a leading cause of respiratory failure requiring mechanical ventilation, but the interaction between sepsis and ventilation is unclear. While prior studies demonstrated a priming role with endotoxin, actual septic animal models have yielded conflicting results regarding the role of preceding sepsis on development of subsequent ventilator-induced lung injury (VILI). Using a rat cecal ligation and puncture (CLP) model of sepsis and subsequent injurious ventilation, we sought to determine if sepsis affects development of VILI. Adult male Sprague-Dawley rats were subject to CLP or sham operation and, after 12 h, underwent injurious mechanical ventilation (tidal volume 30 ml/kg, positive end-expiratory pressure 0 cmH(2)O) for either 0, 60, or 120 min. Biochemical and physiological measurements, as well as computed tomography, were used to assess injury at 0, 60, and 120 min of ventilation. Before ventilation, CLP rats had higher levels of alveolar neutrophils and interleukin-1β. After 60 min of ventilation, CLP rats had worse injury as evidenced by increased alveolar inflammation, permeability, respiratory static compliance, edema, oxygenation, and computed tomography. By 120 min, CLP and sham rats had comparable levels of lung injury as assessed by many, but not all, of these metrics. CLP rats had an accelerated and worse loss of end-expiratory lung volume relative to sham, and consistently higher levels of alveolar interleukin-1β. Loss of aeration and progression of edema was more pronounced in dependent lung regions. We conclude that CLP initiated pulmonary inflammation in rats, and accelerated the development of subsequent VILI.